Endothelial Progenitor Cells for Diagnosis and Prognosis in Cardiovascular Disease. (29th December 2015) - Aragona, Caterina Oriana; Imbalzano, Egidio; Mamone, Federica; Cairo, Valentina; Lo Gullo, Alberto; D'Ascola, Angela; Sardo, Maria Adriana; Scuruchi, Michele; Basile, Giorgio; Saitta, Antonino; Mandraffino, Giuseppe
Abstract : Objective . To identify, evaluate, and synthesize evidence on the predictive power of circulating endothelial progenitor cells (EPCs) in cardiovascular disease, through a systematic review of quantitative studies. Data Sources . MEDLINE was searched using keywords related to "endothelial progenitor cells" and "endothelium" and, for the different categories, respectively, "smoking"; "blood pressure"; "diabetes mellitus" or "insulin resistance"; "dyslipidemia"; "aging" or "elderly"; "angina pectoris" or "myocardial infarction"; "stroke" or "cerebrovascular disease"; "homocysteine"; "C-reactive protein"; "vitamin D". Study Selection . Database hits were evaluated against explicit inclusion criteria. From 927 database hits, 43 quantitative studies were included. Data Syntheses . EPC count has been suggested for cardiovascular risk estimation in the clinical practice, since it is currently accepted that EPCs can work as proangiogenic support cells, maintaining their importance as regenerative/reparative potential, and also as prognostic markers. Conclusions . EPCs showed an important role in identifying cardiovascular risk conditions, and to suggest their evaluation as predictor of outcomes appears to be reasonable in different defined clinical settings. Due to their capability of proliferation, circulation, and the development of functional progeny, great interest has been directed to therapeutic use of progenitor cells in atherosclerotic diseases. This trial is registered with registration number: ProsperoCRD42015023717 .